All that I can fix - Chan, Crystal (Simon Pulse, 2019)
A multiracial fifteen-year-old boy named Ronney lives in Makersville, Indiana with a drug-addicted mother, a suicidally depressed father, and an overly-sensitive younger sister. He's also in love with a perfectionist girl who doesn't love him back. Amidst this turmoil an eccentric man outside of town who collects neglected zoo animals lets the animals out of their cages then kills himself. His sister is then petrified with visions of marauding lions, his parents don't seem to care, his best friend goes on his own personal safari. And in Makersville, a throng of gun control supporters, and gun rights advocates descend, throwing the town into the same chaos Ronney feels.